Meningkatkan Partisipasi Politik Masyarakat Melalui Fungsi Komisi Pemilihan Umum; Studi KPU Kabupaten Sumenep - Ali Armadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine how the General Election Commission implements its duties and functions to increase community political participation in Sumenep Regency. This type of research uses a qualitative descriptive method to provide an overview of implementing the duties and functions of the General Election Commission in increasing community political participation in Sumenep Regency. The researcher interviewed seven people. This research uses three data collection techniques: observation, interviews, and documentation. Meanwhile, data analysis uses data reduction, data presentation, and conclusion. The research results show that implementing the duties and functions of the General Election Commission to increase community political participation in Sumenep Regency is exemplary. Based on the facts and realities in the field, community participation in the simultaneous elections in Sumenep Regency has increased dramatically.